Rainbow Dash and the Daring Do double dare - Berrow, G. M. (New York ; Boston : Little, Brown and Company, 2014)
"Rainbow Dash is a huge fan of the Daring Do book series, but after the newest book comes out, she's not alone! Suddenly, every pony in Ponyville is reading the books! To prove she's' the ultimate fan, Rainbow Dash decides to show her friends that she can be just as brave and "daring" as her hero. But Twilight Sparkle and Rainbow's other friends worry about how far she's willing to go. Just how daring should one pony be?"--
Keywords: Ponies -- Juvenile fiction